The organization of monitoring of future teachers’ psychological and pedagogical training in establishments of professional and technical education - Kryvylova, Olena (ScienceRise: Pedagogical Education, 2020)
In the article there have been theoretically grounded the process of organizationof the monitoring of future teachers’ psychological and pedagogical training in establishments of professional and technical education which consists of five stages: 1 stage – goals and planning of the research; 2 stage – tool development; 3 stage – conducting the research; 4 stage – processing of results; 5 stage – analysis and interpretation of the research results. On the basis of the given components of psychological and pedagogical competence there have been defined three criteria: personal, content and procedural, evaluative and regulatory. Every criterion is a complex of some indexes which characterize the most important and necessary manifestations of components of the psychological and pedagogical competence of future teachers in establishments of professional and technical education. There have been taken the diagnostic tools which give an opportunity to evaluate the levels of formation of components of future teachers’ psychological and pedagogical competence in establishments of professional and technical education according to definite criteria. Diagnostic tools of the cognitive component consist of testing methods: J. Raven test, R. Amthauer test (personal criterion: accordance of psychophysiological peculiarities to professional requirements (mental process: fillings, perception, memory, thinking, imagination and attention)); method of test control, analysis of written and oral answers (content and procedural criterion: theoretical knowledge of academic field (flexibility, strength, understanding); questionnaire of meta-cognitive involvement in the activity (evaluative and regulatory criterion: meta-cognitive knowledge (subject’s knowledge about personal learning strategies), meta-cognitive evaluation (judgments about mental abilities and limitations, their need in a particular situations), meta-cognitive regulation (subject’smodification of thinking). There have been revealed the content of experimental implementation of the method of organizing the psychological and pedagogical training of professional and technical educational establishments’ future teachers (on the example of checking the level of formation of cognitive and meta-cognitive skills, abilities, knowledge and understanding, which have a place in mastering the peculiarities of the psychological and pedagogical activity) and there have been proved the validity and adequacy of the research tools and reliability of the results. The study addresses the problem of labor migration at the level of quality vocational education and training, in particular in the context of the acquisition of higher education qualifiers for personal and professional self-realization, career development throughout life